Implementasi Cross Site Scripting Vulnerability Assessment Tools berdasarkan OWASP Code Review - Muhammad Isfa Hany; Aditya Bhawiyuga; Ari Kusyanti (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Cross site scripting (XSS) attacks is one of the most discovered vulnerabilities in the web application. Unfortunately, not all software engineer and security engineering team fluent aganist all of the web vulnerabilities (Khan et al., 2017). OWASP Code review is a written document explaining about principles, rules, and standards about web application source code analysis. Furthermore, vulnerability assessment process can also aid in more efficient web application vulnerability discoveries. This research will also build a system that can perform vulnerability assessment according to OWASP Code Review. In the system design phase, there are seven regular expression patterns that can help to identify security violation from the chunk of source code and two main regular expressions patterns to find vulnerabilities. Moreover, there are five algorithm design in order to understands how the system will be implemented. The system is implemented with Django Framework and have been tested based on validity, cpu usage, and response time. According to the test result, the system built is better than discovering cross site scripting